A Novel Phase Unwrapping Method Used for Monitoring the Land Subsidence in Coal Mining Area Based on U-Net Convolutional Neural Network - Wang, Zhiyong; Li, Lu; Yu, Yaran; Wang, Jian; Li, Zhenjin; Liu, Wei (Frontiers in Earth Science, 2021)
Large-scale and high-intensity mining underground coal has resulted in serious land subsidence. It has caused a lot of ecological environment problems and has a serious impact on the sustainable development of economy. Land subsidence cannot be accurately monitored by InSAR (Interferometric synthetic aperture radar) due to the low coherence in the mining area. In order to solve this problem, a novel phase unwrapping method based on U-Net convolutional neural network was constructed. Firstly, the U-Net convolutional neural network is used to extract edge to automatically obtain the boundary information of the interferometric fringes in the region of subsidence basin. Secondly, an edge-linking algorithm is constructed based on edge growth and predictive search. The interrupted interferometric fringes are connected automatically. The whole and continuous edges of interferometric fringes are obtained. Finally, the correct phase unwrapping results are obtained according to the principle of phase unwrapping and the boundary of interferometric fringes. The Huaibei Coalfield in China was taken as the study area. The real interferograms from D-InSAR (differential interferometric synthetic aperture radar) processing used Sentinel-1A data were used to verify the performance of the new method. Subsidence basins with clear interference fringes, interrupted interference fringes and confused interference fringes are selected for experiments. The results were compared with the other methods, such as MCF (minimum cost flow) method. The tests showed that the new method based on U-Net convolutional neural network can resolve the problem that is difficult to obtain the correct unwrapping phase due to interrupted or confused interferometric fringes caused by low coherence in the coal mining area. Hence, the new method can help to monitor the subsidence in mining areas under different conditions using InSAR technology accurately.